An Analysis of Virtual Flux Direct Power Control of Three-Phase AC-DC Converter - Nor Azizah Mohd Yusoff; Azziddin M. Razali; Kasrul Abdul Karim; Auzani Jidin; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper presents an analysis of virtual-flux direct power control (VFDPC) technique for the three-phase pulse width modulation (PWM) ac-dc converter. The proposed VFDPC is developed by assuming the grid voltage and converter line filters quantities are related to a virtual three-phase ac motor. The controller works with less number of sensors by eliminating the voltage sensors used for measuring the three-phase grid voltage. The grid virtual flux which is proportional to the grid voltage will be estimated from the information of converter switching states, line current, and dc-link output voltage. Several analyses are performed in order to study the steady state and dynamic performance of the converter, particularly during the load and DC voltage output reference variations. The proportional integral (PI) controller at the outer voltage control loop of VFDPC is tuned properly and the entire PWM ac-dc converter system is simulated using MATLAB/Simulink to ensure the dc output voltage follow the desired output voltage under steady state and dynamic conditions. Ac-dc converter utilizing the proposed VFDPC is able to generate three-phase input current waveforms that are almost sinusoidal with low harmonics contents which is less than 5% and near unity power factor (pf) operation.